Synthetic Triterpenoids Can Protect against Toxicity without Reducing the Efficacy of Treatment with Carboplatin and Paclitaxel in Experimental Lung Cancer - Karen T. Liby (SAGE Publishing, 2014)
Synthetic oleanane triterpenoids are multifunctional drugs being developed for the prevention and treatment of a variety of chronic diseases driven by inflammation and oxidative stress. Low nanomolar concentrations of triterpenoids inhibit the induction of inflammatory cytokines, and these drugs are potent activators of the Nrf2 cytoprotective pathway. In contrast, low micromolar concentrations of triterpenoids increased the production of ROS and induced apoptosis in a dose-dependent manner in malignant MCF10 CA1a breast cancer cells. Because cancer cells respond differently to ROS than normal cells, it should be possible to exploit these differences therapeutically. In an experimental model of lung cancer, the triterpenoids activated the Nrf2 pathway, as seen by induction of the cytoprotective enzyme NQO1, and reduced the toxicity of carboplatin and paclitaxel. The induction of the Nrf2 pathway in the lung did not suppress the efficacy of treatment with carboplatin and paclitaxel, as the average tumor burden in the group treated with the combination of CDDO-Me and carboplatin/paclitaxel decreased by 90% (P < 0.05 vs. the controls and both single treatment groups). Understanding the dose response of triterpenoids and related drugs will help provide the proper context for optimizing their potential clinical utility.